UPAYA THAILAND DALAM PENANGGULANGAN DRUGS TRAFFICKING MENUJU DRUG-FREE ASEAN 2015 - Siregar, Riduwan Effendi; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Thailand Efforts on Preventing Drugs Trafficking Towards Drug - Free ASEAN 2015. The research aimed to determine the efforts that have been made by Thailand in tackling the problem of drugs trafficking. The theory is used to study this problem is the Global Epidemic Model (GEM). The hypothesis of this study is suspected because of the impetus towards a Drug- Free ASEAN 2015. The research using qualitative methods and library research. The research data was obtained from books, journals, working papers, articles, official documents, and websites. Based on the data obtained from these sources, researchers can obtain the result of the efforts of Thailand. The Joint Declaration for A Drug - Free ASEAN 2015 made Thailand seeks to combating drug trafficking, drug cultivation and drug networks that deploy domestically and internationally, by continuously launching the war on drugs, making strategies in controlling drug trafficking, strengthen laws governing drug, assist treatment and rehabilitation and sustainable alternative development based on cooperation with countries that have similar problems related to drug problems in the world.Keyword: Drugs Trafficking, Drug-Free ASEAN 2015, Global Epidemic Model.